Інвестиції домогосподарств як джерело їх фінансової стійкості - Качула, Світлана Валентинівна; Kachula, Svitlana; Лисяк, Любов Валентинівна; Lysiak, Liubov (Чорноморський національний університет імені Петра Могили, ТОВ "ДКС Центр", 2023)
У статті досліджено сутність інвестицій домогосподарств як джерела їх фінансової стійкості. Встановлено, що домогосподарство з фінансовою стійкістю має здатність генерувати достатні доходи, ефективно керувати своїми витратами та зберігати резервні фонди. Тобто, фінансово стійке домогосподарство має достатній рівень накопичених заощаджень або інвестицій, які можуть використовуватися в разі фінансових негараздів або несподіваних витрат. Проведений аналіз динаміки заощаджень у доходах домогосподарств показав, що в 2019 р. та 2021 р. спостерігається від’ємний приріст заощаджень, що негативно вплинуло на фінансову стабільність домогосподарств, а з 2022 р. спостерігається переоцінка фінансової стійкості домогосподарств, при якій 40% домогосподарств вважає, що заощаджень вистачить на короткий термін. Доведено, що фінансова стійкість дозволяє домогосподарству впоратися з непередбачуваними подіями, такими як втрата роботи, медичні та інші несподівані витрати, економічні кризи або зміни в ринкових умовах. Інвестиційний потенціал населення вказує на здатність і готовність домогосподарств вкладати свої фінансові ресурси в різні види інвестицій з метою отримання майбутніх доходів і збільшення свого капіталу. Інвестиційна стратегія повинна відповідати фінансовим цілям та індивідуальним потребам домогосподарства. The article examines the essence of household investments as a source of its financial stability. A financially sound household has been found to have the ability to generate sufficient income, manage its expenses effectively, and maintain reserve funds. That is, a financially stable household has a sufficient level of accumulated savings or investments that can be used in case of financial difficulties or unexpected expenses. The analysis of the structure of aggregate household resources showed that starting from 2020, the share of wages in the structure of aggregate household resources has been decreasing. This was influenced by the COVID-19 pandemic, when most household members were forced to switch to a remote form of work. The full-scale invasion of Russia on the territory of Ukraine reflected not only on the economy of Ukraine and business, but also on households. In 2019 and 2021, there is a negative increase in household savings, which negatively affected the financial stability of households, and from 2022, a reassessment of the financial stability of households is observed, in which 40% of households believe that savings will be enough for the short term. Financial resilience has been shown to enable a household to cope with unforeseen events such as job loss, medical and other unexpected expenses, economic crises or changes in market conditions. A financially stable household can maintain stability in its life, reducing financial stress and risks of debt burden. The investment potential of the population indicates the ability and willingness of households to invest their financial resources in various types of investments in order to obtain future income and increase their capital. Regardless of the chosen direction of investment, it is important to conduct a detailed analysis, understand the risks and potential income, as well as be ready for long-term investments. The investment strategy should meet the financial goals and individual needs of the household. Creating emergency funds that can be used for contingencies is an important step in ensuring the financial stability of households during martial law. These funds can be used to cover the costs of emergency, medical services or evacuation if necessary. It is important to note that specific tools to support the financial stability of households under martial law may vary depending on government policies and available resources. Therefore, careful analysis of the situation, planning and consideration of risks are important elements of ensuring the financial stability of households in the conditions of martial law.
Investments of households as a source of their financial stability
Keywords: домогосподарства; households; фінанси домогосподарств; household finances; фінансова стійкість; financial sustainability; заощадження; savings; інвестиції; investments; інвестиційні ресурси; investment resources; інвестиційний ризик; investment risk; інвестиційна стратегія; investment strategy